Advanced Characterization Techniques Paving the Way for Commercialization of Low‐Cost Prussian Blue Analog Cathodes. (5th November 2021) - Liu, Xiao‐Hao; Peng, Jian; Lai, Wei‐Hong; Gao, Yun; Zhang, Hang; Li, Li; Qiao, Yun; Chou, Shu‐Lei
Abstract: Prussian blue analogs (PBAs), as promising cathode materials for sodium‐ion batteries (SIBs), have received extensive research interest due to their appealing characteristics, e.g., the low cost of their raw materials, easy manufacturing, open frameworks, and high theoretical specific capacity. There are some challenges for PBAs cathodes, however, hindering their performance output, making them currently unacceptable for practical applications. To improve the performance and cycling stability of PBAs, a clear in‐depth understanding of the relationship of their electrochemical reaction process to their ion insertion/extraction mechanisms and structural evolution is extremely important. Nowadays, advanced characterization techniques have become an important tool to guide the construction of high‐performance PBAs cathodes. In this review, the various advances by using advanced characterization techniques to reveal the reaction mechanisms for PBAs cathodes are summarized and discussed. By appreciating how the advanced characterization techniques to guide fabrication of high‐performance PBAs or reveal their detailed reaction mechanisms, it is hoped that this review can assist readers to find more valuable and advanced technologies to help to resolve some key problems and enhance their performance so as to accelerate the practical application of PBAs cathode for SIBs. Abstract : A comprehensive summary of the advantages and challenges and the most used in situ and ex situ techniques paving the way for commercialization of low‐cost Prussian blue analog cathodes for sodium‐ion batteries is presented.